PO-63 - Exhausted platelets in cancer patients with high risk of venous thromboembolism and poor prognosis. Issue 140 (April 2016) - Riedl, J.; Kaider, A.; Marosi, C.; Prager, G.; Eichelberger, B.; Koder, S.; Panzer, S.; Pabinger, I.; Ay, C.
Abstract : Introduction: Platelets play a crucial role in cancer development, progression and metastatic spread of malignancy. In vitro data show that cancer cells have the ability to activate platelets, and clinical studies found increased levels of platelet activation markers in cancer patients. Moreover, platelets are thought to be involved in the development of venous thromboembolism (VTE) in cancer patients, a frequent complication of malignant disease associated with high morbidity and mortality. Aim: In this study, we aimed to examine the activation status of platelets in cancer patients and investigate the association with risk of future venous thromboembolism (VTE) and mortality. Materials and Methods: In a prospective observational cohort study of cancer patients we measured pre-chemotherapy platelet P-selectin and glycoprotein (GP) IIb/IIIa expression and monocyte-platelet aggregates (MPA) in vivo and in response to ex vivo stimulation of the platelet activation receptors protease-activated receptor (PAR) -1, -4, and GPVI by whole blood flow cytometry. Primary and secondary endpoints of the study were occurrence of objectively confirmed VTE and death during 2-year follow-up, respectively. Results: Out of 62 patients (median age [interquartile range, IQR]: 63 [54-70] years, 48% female) with cancers of the pancreas (n = 19), lung (n = 18), brain (n = 14), colon (n = 8) and stomach (n = 3), 9 (14.5%) developed VTE and 32 (51.6%) died. P-selectin, activated GPIIb/IIIa expression and MPA formation did not significantly differ between tumor sites (Kruskal Wallis test). Reduced platelet responsiveness to PAR-1 and GPVI stimulation was associated with a higher risk of VTE (hazard ratio [HR] per decile increase in %P-selectin positive platelets: 0.73 [95% confidence interval: 0.56-0.92, p = 0.007] and 0.77 [0.59-0.98, p = 0.034], respectively; Table 1). Further, lower platelet P-selectin and activated GPIIb/IIIa expression in vivo and in response to PAR-1, -4 and GPVI stimulation, but not MPA formation, were associated with a higher risk of death (Table 1). Conclusions: Cancer patients with a poor prognosis had degranulated platelets, presumably as a consequence of previous activation. Our data suggest that platelets' continuous activation and thus exhaustion is involved in cancer-associated VTE and cancer mortality. Table 1 Platelet activity and risk of VTE and death in 62 cancer patients. Hazard ratios (HR) and 95% confidence intervals (CI) for the increase per decile in each parameter are given   Stimulated via Risk of VTE Risk of death HR (95% CI) p HR (95% CI) p P-selectin expression (%positive platelets) - 0.92 (0.72-1.15) 0.438 0.88 (0.78-0.99) 0.046   PAR-1 0.73 (0.56-0.92) 0.007 0.87 (0.77-0.98) 0.027   PAR-4 0.89 (0.70-1.12) 0.307 0.83 (0.73-0.95) 0.007   GPVI 0.77 (0.59-0.98) 0.034 0.84 (0.74-0.96) 0.011 Activated GPIIb/IIIa expression (%positive platelets) - 0.97 (0.77-1.23) 0.817 0.83 (0.73-0.95) 0.007   PAR-1 0.76 (0.57-0.97) 0.025 0.89 (0.78-1.01) 0.067   PAR-4 0.90 (0.71-1.13) 0.355 0.82 (0.72-0.94) 0.004   GPVI 0.79 (0.59-1.02) 0.065 0.84 (0.73-0.97) 0.015 Monocyte-platelet aggregates (%monocytes carrying platelets) . 0.88 (0.69-1.10) 0.266 1.02 (0.90-1.14) 0.811   PAR-1 0.78 (0.59-1.00) 0.046 0.96 (0.85-1.09) 0.563   PAR-4 0.85 (0.66-1.07) 0.169 0.99 (0.88-1.13) 0.951   GPVI 0.79 (0.59-1.00) 0.052 1.01 (0.89-1.14) 0.927